1991
DOI: 10.1093/jee/84.4.1270
|View full text |Cite
|
Sign up to set email alerts
|

Economic Effects of Horn Fly (Diptera: Muscidae) Populations on Beef Cattle Exposed to Three Pesticide Treatment Regimes

Abstract: Horn flies could not be maintained below 50 per animal with sprays or dusts during a 21-wk study. However, weights of cows and calves and condition scores of cows were not influenced by suppression of Haematobia irritans (L.) populations. Results show that cattle in northwest Florida can tolerate average populations of greater than or equal to 200 flies for 70 d with no adverse economic effects. Spray treatments providing the best fly control were Lintox-D and Ra-Vap. The most economical products for use were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0
3

Year Published

1999
1999
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 12 publications
1
18
0
3
Order By: Relevance
“…The signiÞcant reduction in horn ßy numbers at SEREC to a mean of Ϸ150 ßies per cow resulted in a signiÞcant increase in calf weaning weight. The tactics used at SWREC (excluding Brahman crossbreeding) reduced horn ßy numbers to levels (Ն200 ßies per cow) that were similar to levels that were achieved in previously published studies (Brethour et al 1987, Schreiber et al 1987, Hogsette et al 1991 where no economic weaning weight advantage was associated with horn ßy management.…”
Section: Table 2 Results Of F Tests Of the Main Effects And Interactsupporting
confidence: 68%
“…The signiÞcant reduction in horn ßy numbers at SEREC to a mean of Ϸ150 ßies per cow resulted in a signiÞcant increase in calf weaning weight. The tactics used at SWREC (excluding Brahman crossbreeding) reduced horn ßy numbers to levels (Ն200 ßies per cow) that were similar to levels that were achieved in previously published studies (Brethour et al 1987, Schreiber et al 1987, Hogsette et al 1991 where no economic weaning weight advantage was associated with horn ßy management.…”
Section: Table 2 Results Of F Tests Of the Main Effects And Interactsupporting
confidence: 68%
“…As diferenças de ganhos de peso médio foram de 7, 1, 2 e 3 kg para as vacas e de 3, 2, 1 e 2 kg para os bezerros à desmama, no primeiro, segundo, terceiro e quarto ano, respectivamente. Estes resultados indicam que o nível de infestação da mosca produziu pouco efeito no ganho de peso de vacas e bezerros Nelore antes da desmama e são similares aos obtidos por outros estudos (Schreiber et al 1987, Hogsette et al 1991, Morrison & Foil 1995. Os resultados diferem dos estudos realizados por Kunz et al (1984), Quisenberry & Strohbehn (1984), Haufe (1986), Steelman et al (1991) e Suarez et al 1995, que encontraram diferenças significativas no ganho de peso de vacas e bezerros tratados contra a mosca-dos-chifres.…”
Section: Resul Resul Resul Resul Results T T T Tados E Discus Ados E Dunclassified
“…However, certain insecticides are restricted from use on lactating dairy cattle. Furthermore, Hogsette et al (1991) found alternative insecticide treatments (organophosphate class) were not able to reduce ßy densities to Ͻ50 ßies per head, nor did the use of insecticides affect weight gains. They surmised that the elimination of the horn ßy was not possible in Florida and perhaps management around a 200 ßy threshold was an attainable objective with added beneÞts to resistance management and reduced pesticide use (Hogsette et al 1991).…”
mentioning
confidence: 97%
“…Horn ßy densities of several hundred ßies per animal are common among uncontrolled populations. Proposed economic thresholds for horn ßies on cattle vary from 50 (Butler and Okine 1999) to 230 per animal (Haufe 1979); however, 200 ßies per animal is the generally accepted standard (Schreiber et al 1987, Hogsette et al 1991.…”
mentioning
confidence: 99%
See 1 more Smart Citation